2023
DOI: 10.3390/ma16196514
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Various Nanomaterials on the Rheology and Hydration Kinetics of Oil Well Cement

Michael Boniface Baragwiha,
Kenedy Geofrey Fikeni,
Yukun Zhao
et al.

Abstract: Nanomaterials have great potential to influence the properties of cement-based materials due to their small particle size and large specific surface area. The influences of Nano-SiO2 (NS), gamma-nano-Al2O3 (GNA), alpha-nano-Al2O3 (ANA), and nano-TiO2 (NT) on the rheology and hydration kinetics of class G cement at 30 °C were investigated in this study. The nanomaterials were added in dry powder form at dosages of 1, 2, 3, 5, and 7% by weight of cement (bwoc), and their dispersion was accomplished using polycar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…15 Another author reported that the structurebuilding ability of cement slurries was substantially enhanced by the addition of nano-SiO 2 (NS) and gamma-nano-Al 2 O 3 (GNA), as demonstrated by the increased values of apparent viscosity, gel strength, and yield stress. 16 Dieder et al reported that gilsonite-enriched cement can result in maintaining the mechanical integrity and reduces the permeability of the cement core, which implicates potential gas mitigation. 17 Another author found that gilsonite-based cement core exhibited 20% decrease in porosity compared to cement core without gilsonite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Another author reported that the structurebuilding ability of cement slurries was substantially enhanced by the addition of nano-SiO 2 (NS) and gamma-nano-Al 2 O 3 (GNA), as demonstrated by the increased values of apparent viscosity, gel strength, and yield stress. 16 Dieder et al reported that gilsonite-enriched cement can result in maintaining the mechanical integrity and reduces the permeability of the cement core, which implicates potential gas mitigation. 17 Another author found that gilsonite-based cement core exhibited 20% decrease in porosity compared to cement core without gilsonite.…”
Section: Introductionmentioning
confidence: 99%
“…Bayanak et al investigated that 0.5% nanosilica enhances compressive strength by 91% and reduces fluid loss by 77% of cement slurry . Another author reported that the structure-building ability of cement slurries was substantially enhanced by the addition of nano-SiO 2 (NS) and gamma-nano-Al 2 O 3 (GNA), as demonstrated by the increased values of apparent viscosity, gel strength, and yield stress . Dieder et al reported that gilsonite-enriched cement can result in maintaining the mechanical integrity and reduces the permeability of the cement core, which implicates potential gas mitigation .…”
Section: Introductionmentioning
confidence: 99%
“…The use of NMs to improve the performance improvement of materials has been proven in many research areas [12,13]. As for the CBM system, the traditional NMs include nano-silica (NS), nano-calcium carbonate (NC), and nano-metakaolin (NMK) [14][15][16], and the utilization of these NMs is becoming a research hotspot for improving the performance of CBMs. To be specific, NS is a typical NM possessing great pozzolanic activity, filler effect, and crystal core effect; when it is used as a reinforcing material inside CBMs, it exhibits great potential for improving the performance of the material based on the above advantages.…”
Section: Introductionmentioning
confidence: 99%